Revision of Ommatius Wiedemann (Diptera: Asilidae). IV. Pygommatius subgen. nov. with twenty-five Afrotropical species - Scarbrough, Aubrey G.; Marascia, Claudio G. (Zootaxa, 2003)
A new subgenus of Ommatius Wiedemann, Pygommatius subgen. nov., is described. Twenty-five Afrotropical species are assigned to this subgenus including O. albatus Martin, O. bingeri Oldroyd, O. brevicornis Curran, O. caligula Oldroyd, O. cingulatus Bromley, O. dasypogon Oldroyd, O.digittatus Oldroyd, O. jaculator Oldroyd, and O. neglectus Bromley, and the following new species: O. alatipes, O. comosus, O. fluvius, O. grossus, O. imaginus, O. limbus, O. litoreus, O. lulua, O. magnipes, O. pectinus, O. porticus, O. renudus, O. segouensis, O. strigiatus, O. talus, and O. vultus. Twenty-three species are placed in the following six species groups: the bingeri, the brevicornis, the comosus, the grossus, the litoreus, and the pectinus groups. Ommatius ornatipes (Engel) is officially recognized as a secondary homonym of O. ornatipes Becker, and O. neglectus Bromley a junior synonym of O. ornatipes (Engel) (SYN. N.). Since Ommatius ornatipes (Engel) is preoccupied by O. ornatipes Becker, O. neglectus is recognized as the next available name for O. ornatipes (Engel). The male of O. brevicornis and the female of O. albatus are described and illustrated for the first time. Illustrations of morphological structures, descriptions, and a key to all species are provided, as well as brief comments on the distribution of the group.